ANALYSIS OF THE PREVALENCE OF ACUTE PYELONEPHRITIS IN THE ALTAI TERRITORY FOR A LONG-TERM OBSERVATION PERIOD - Ананьев, Владимир Александрович; Лубянский, Владимир Григорьевич; Субботин, Евгений Александрович (Medicine in Kuzbass, 2023)
The aim of the study – was to study and analyze the incidence of acute pyelonephritis of the female and male population of the Altai Territory for 7 years (2014-2020). Materials and methods. The circulation of the population of the Altai Territory with a diagnosis of acute pyelonephritis for 7 years (the period from 2014 to 2020) was studied and analyzed. A copy of the data was carried out from the annual form provided to the chief urologist of the Altai Territory by the interdistrict departments of urology in the form of a «Report on the work of the urology department». The study was conducted by a continuous method. Indicators of the primary incidence of acute pyelonephritis, the percentage of transition to destructive forms of acute pyelonephritis, and the number of nephrectomies performed were obtained. Results. Based on the results of the study, it can be concluded that in the Altai Territory the number of cases of diagnosed acute pyelonephritis does not differ fundamentally from the all-Russian rate per 100 000 population. A very high level of deaths of patients of working age has been determined since 2017 with a tendency to reduce the age to 60 years from sepsis and its complications. Conclusion. The proportion of destructive forms of acute pyelonephritis remains consistently high throughout the study period. This is due to the untimely and late diagnosis of acute pyelonephritis at the stages of primary care of the Central District Hospital and interdistrict urological departments, which leads to a pronounced deterioration in indicators.